Collaborative Governance Process for Tourism Village Development in Semen Gandusari Village, Blitar Regency - Styareni, Ayu Apriliana Puspita; Suryawati, Dina; Prasetyo, Franciscus Adi (Raudhah Publisher, 2024)
The research entitled